Circular RNA TAF4B targeting MFN2 accelerates cell growth in bladder cancer through p27 depression and AKT activation - Zhang, Xiaoting; Xu, Jia; Zhuang, Guangzhen; Wang, Yiting; Li, Xiaofeng; Zhu, Xiaohui (Frontiers in Immunology, 2024)
Bladder cancer (BCa) is a common urinary tract malignancy, distinguished by its high recurrence rate and the frequent necessity for microscopic examination, which presents significant challenges to clinical management. Our previous studies revealed that circular TAF4B (circTAF4B) is markedly overexpressed in BCa and is linked to an unfavorable prognosis. However, the precise targets and molecular mechanisms by which circTAF4B influences BCa have yet to be fully elucidated. In this research, employing RNA pull-down assays coupled with mass spectrometry, we have discovered Mitofusin 2 (MFN2) as a novel binding partner for circTAF4B. Utilizing siRNA to deplete MFN2, we observed an enhancement in the suppressive effects of circTAF4B overexpression on the proliferation and migration of BCa cells. Moreover, the use of circTAF4B shRNA lentiviral particles impeded the progression of BCa by inducing the expression of p27 and inactivating the AKT signaling pathway. In summary, the physical interaction between circTAF4B and MFN2 is a critical event in the tumorigenesis and progression of BCa. Targeting circTAF4B or its associated molecular complexes may offer a promising therapeutic strategy for the diagnosis and treatment of BCa